People United to Sustain Health (PUSH): A Community‐Based Participatory Research Study - Betty M. Kennedy; Peter T. Katzmarzyk; William D. Johnson; Glenda S. Johnson; Bernestine B. McGee; Catherine M. Champagne; David W. Harsha; Terri Crawford; Donna H. Ryan (Wiley, 2014)
Abstract The prevention of weight gain to address the obesity epidemic rather than weight loss involves promoting small changes in food choices and physical activity. People United to Sustain Health (PUSH) was designed to increase fruit and vegetable consumption, physical activity, and food security to prevent weight gain in rural adults. Forty‐nine participants were randomized into a treatment group which received access to a "Rolling Store," nutrition education and physical activity, and a control group which received family coping classes. Forty‐one (84%) of participants completed the study. At the end of 6 months, weight for all participants was maintained from baseline to completion with no significant differences between the groups. The mean fruit consumption over 6 months for the treatment group increased and was significantly greater than change in the control group (p = 0.01). This community‐based participatory research study was considered successful because weight gain was prevented.